Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Project Based Learning (PjBL) di SMP Negeri 1 Sungai Pinyuh Kabupaten Mempawah - Sasmita Sasmita (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Classroom Action Research was conducted in the subject of Catholic Religious Education and Character Building for Grade VII at SMP Negeri 1 Sungai Pinyuh, Mempawah Regency, with the aim of implementing the Project Based Learning (PjBL). The PjBL model was chosen because it has the potential to encourage active student involvement in the learning process by completing projects that are relevant to the subject matter. This research is a Classroom Action Research (CAR) consisting of two cycles. The subjects of the research were 12 seventh-grade students.The research results show that in Cycle I, the average score was 73.33, categorized as Fair. Meanwhile, in Cycle II, the average score increased to 86.67, categorized as Good. Although there was still one student in Cycle II who had not yet met the required standard, the class-wide mastery of 80% was achieved, and the student in question participated in independent remedial activities. The improvement in students' post-test scores can be seen from the average score. The average score increased from 73.33, categorized as Fair, to 86.67, categorized as Good, with a 33.33% increase in student mastery. Thus, the PjBL model is effective in improving learning outcomes and student involvement in the learning process at SMP Negeri 1 Sungai Pinyuh.